Histology of the digestive tract of three species of sea cucumber Isostichopus badionotus, Stichopus sp. and Stichopus hermanni (Aspidochirotida: Stichopodidae). - Vergara, Wensy (2015)
Sea cucumbers have an important ecological role in the marine environment because they are able to process organic and inorganic matter, which contributes to the oxygenation and energy transfer in the ecosystem. In general, there is a lack of knowledge on the basic morphology of native species of sea cucumber and the function of vital organs. The aim of this study was to describe the histology of the digestive tract (DT) of three species of holothuroids from Rodadero Bay, Colombia. Thirty specimens of Isostichopus badionotus, Stichopus sp. and Stichopus hermanni were obtained and sacrificed by hypothermia. In the laboratory, sections of foregut, midgut and hindgut were obtained and fixed in formalin (10%) for later conventional histological processes; besides, some samples were fixed in glutaraldehyde (3%) for their inclusion in resins and studies in high resolution and electron microscopy. For the studied species, the DT is long, folded, and is distributed in the coelomic cavity; it has at least twice the length of the sea cucumber body. The DT presents villi lined by a columnar pseudostratified ciliated epithelium, which rests on a basement membrane and a layer of collagen fibers. Four types of cells were identified: coelocmocytes, brown cells, enterocytes and mucous cells, and the spicules were evident throughout the digestive tract tissue. Light microscopy showed elongated inclusions of calcareous formation located essentially in the hindgut, "the psamoma bodies". We observed granular mucous cells with an apical surface with numerous microvilli. The histology of the DT of I. badionotus, Stichopus sp. and S. hermanni were found to be similar, but we found differences (p<0.05) in the thickness of the intestinal submucosa tissue, which can be tied to specific feeding habits of each species. Characterization of the morphohistology of the digestive tract of sea cucumber is a useful tool to understand their feeding physiology.